Family physicians’ perceptions of the value of medical student training in primary health care at facilities allocated to Stellenbosch University final year medical students in the Cape Metropole - Murphy, Levern (Stellenbosch : Stellenbosch University, 2022)
Thesis (MFamMed)--Stellenbosch University, 2022.